Modeling of the Effect of Zeolite Concentration on the Biological Nitrification Process in the Presence of Sulfide and Organic Matter - Huilinir-Curio, C; Montalvo-Martinez, S; Acosta-Cordero, L; Palominos-Acosta, N (Bellwether Publishing, Ltd., 2020)
The evaluation of the nitrification kinetics in the simultaneous presence of sulfide and organic matter using zeolite as improver was the main goal of this work. According to the sensitivity and collinearity analyses, five parameters were the most sensitive in the model, whose calibrated values were: μ max, AOB = 0.02642 ± 0.002 h−1; μ max, NOB = 0.3307 ± 0.416 h−1; K S,NOB = 1.65·10−6 ± 2.85·10−6 mgHNO2-N/L; k S2 = 0.8213 ± 0.076 and n = 0.6537 ± 0.030. A good fit between the experimental data and the model’s results including the effect of zeolite on the kinetic parameters was obtained, with Theil inequality coefficient values between 0.109 and 0.007 for all the variables studied, with all of these values lower than 0.3. Thus, the model proposed is robust and can simulate the nitrification process in the presence of sulfide and organic matter when zeolite was used as improver. © 2020 Taylor & Francis Group, LLC.